Reviews of Books (International review of mission, 1942)
Book reviewed in this article: A MISSIONARY PIONEER IN MADAGASCAR: HENRY RUSILLON, MISSIONNAIRE À MADAGASCAR (1872–1938). By J. E. SIORDET. CHRISTIAN RE-UNION: CHRISTIAN RE-UNION: A Plea for Action. By HUGH MARTIN. CHRISTIAN RE-UNION: LAY CELEBRATION OF THE LORD'S SUPPER: A Congregationalist Point of View. By H. C. LEFEVER. CHRISTIAN RE-UNION: LAY ADMINISTRATION OF THE LORD'S SUPPER: A Methodist Point of View. By A. MARCUS WARD. CHRISTIANITY AND INTERNATIONAL AFFAIRS: SURVEY OF INTERNATIONAL AFFAIRS, 1938. Volume I. By ARNOLD J. TOYNBEE, assisted by V. M. BOULTER. CHRISTIANITY AND INTERNATIONAL AFFAIRS: DOCUMENTS ON AMERICAN FOREIGN RELATIONS, Volume III: July 1940-June 1941. Edited by S. SHEPARD JONES and DENYS P. MYERS. CHRISTIANITY AND INTERNATIONAL AFFAIRS: A LETTER TO GREAT BRITAIN FROM SWITZERLAND. By KARL BARTH. CHRISTIANITY AND INTERNATIONAL AFFAIRS: THE CONTRIBUTION OF THE CHURCHES TO THE RECONSTRUCTION OF EUROPEAN LIFE. By P. S. GERBRANDY. THE TRANSFORMATION OF A CIVILIZATION INTO A NATION: THE CHINA OF CHIANG K'AI-SHEK: A Political Study. By PAUL M. A. LINEBARGER. THE TRANSFORMATION OF A CIVILIZATION INTO A NATION: CHINA THEN AND NOW. By JEAN ESCARRA. THE BATTLE FOR ASIA: THE BATTLE FOR ASIA. By EDGAR SNOW. THE BATTLE FOR ASIA: THE STRUGGLE FOR NORTH CHINA. By GEORGE E. TAYLOR. THE BATTLE FOR ASIA: JAPAN SINCE 1931. By HUGH BORTON. JAPAN UNMASKED: JAPAN UNMASKED. By HALLETT ABEND. JAPAN IN THE WORLD CRISIS: JAPAN IN THE WORLD CRISIS. By C. J. STRANKS. A JAPANESE CHRISTIAN EDUCATIONIST: MY LANTERN. By MICHI KAWAI. THE TRAINING OF THE COMMUNITY NURSE: NURSING EDUCATION RELATED TO THE CULTURAL BACKGROUND IN EAST AND SOUTH-EAST AFRICAN COLONIES. BY JANET WELCH, M.B.E. TRIBAL GOVERNMENT IN THE SUDAN: THE POLITICAL SYSTEM OF THE ANUAK OF THE ANGLO-EGYPTIAN SUDAN. By E. E. EVANS-PRITCHARD; Ph.D. SOUTH AFRICAN HISTORY: A HISTORY OF SOUTH AFRICA: SOCIAL AND ECONOMIC. By C. W. DE KIEWIET. LATIN AMERICA: GOOD NEIGHBORS. By HUBERT HERRING. LATIN AMERICA: BRAZIL, LAND OF THE FUTURE. By STEFAN ZWEIG. WOMAN IN ISLAM: WOMAN IN ISLAM: A Manual with Special Reference to Conditions in India. By V. R. and L. BEVAN JONES. CULTURE CHANGE IN SOUTH INDIA: CULTURE CHANGE AND THE UNDERPRIVILEGED. By A. T. FISHMAN, Ph.D. A JEWISH-CHRISTIAN DEBATE: DAS CHRISTLICHE VERSTÄNDNIS DES ALTEN TESTAMENTS UND DER JÜDISCHE EINWAND. By GEORGE L. B. SLOAN and SCHALOM BEN-CHORIN. THE END OF AN EPOCH IN JAPAN: THE JAPAN CHRISTIAN YEAR BOOK, 1941. Edited by DARLEY DOWNS.